Program Pemetaan dan Urgensi Penanganan Masalah Sosial Pada Wilayah Bukan Pesisir di Kabupaten Gresik, Jawa Timur - Edy Supriyadi; Iha Haryani Hatta (Jurnal Pengabdian Pada Masyarakat, 2018)
PROGRAM OF MAPPING AND URGENCY OF HANDLING SOCIAL PROBLEMS IN NON-COASTAL AREAS IN GRESIK REGENCY, EAST JAVA. This program aims to determine the geography, demography, psychography, economic, and socio-cultural conditions, as well as the urgency of handling social problems. The study used 100 respondents consisted of 20 respondents for 5 villages. Analysis used Descriptive and SWOT. The results of the study include land altitude between 3-4 meters from sea level, rarely rain, lowland, and hot weather; densely populated with nearly equal female population with men; the community is actively learning and carrying out the religious activities that are followed and the means of worship are good and complete; most of the conditions of the region have not supported the welfare of the population and regional development; village heads have a big influence and high role for society. Each region has the urgency of handling different problems but the main problem to be addressed is inadequate facilities and infrastructure, environment, lack of development of SME.